Avaliação da legislação brasileira do uso conjugado de água de chuva - Maebara, Andre Kazunori (2018)
With the growth of cities and the great urban concentration, problems like the lack of water and urban drainage begin to occur. To reduce this problem, the use of rainwater begins to be proposed in legislation with the objective of rational use of drinking water and the reduction or control of floods. The importance of the study of municipal laws, together with the norms, is justified in order to identify and standardize the parameters and guidelines that allow the combined use of rainwater, considering retention and utilization. The objective of this work is to evaluate the feasibility of applying municipal legislation for the retention and utilization of rainwater in urban lots by means of the identification of the guidelines contained in the laws and the respective parameterization with the technical standards. Through the bibliographical survey of the legislation, the study was made to elucidate the important points and parameters, making the comparison between laws and norms applying the parameters in different typologies of houses for the cities of São Paulo and São José do Rio Preto, and also the scales, according to legislation to verify if they meet the demand and retention of rainwater. Among the nine parameters analyzed, only three of them, the dimensioning, the use of rainwater and the application of the legislations, are presented in detail, the remaining parameters are just mentioned. In the sizing the equations contained in the laws use variables such as impermeable area of coverage and terrain. There is also the rainfall index and rainfall, but are used as constants. For the sizing according to the standard, variables such as rainfall index and demand are used. The potential for utilization has been shown that for large reservoir volumes it is biased towards the detention of rainwater, although, with large reservoir volumes, the rainwater harvesting system can make both the use of rainwater when water in the lot. Finally, even in the case of rainwater retention legislation, it is possible to make use of it according to the law.